2015
DOI: 10.21776/ub.mps.2015.001.01.2
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Tayangan Humor Terhadap Short Term Memory pada Mahasiswa Baru

Abstract: Tujuan dari penelitian ini adalah untuk pengetahui pengaruh tayangan humor terhadap short term memory. Metode humor mampu mengurangi hormon kortisol dan hormon epinephrine sehingga informasi yang diterima dapat diantar ke otak untuk proses storage dan recall. Metode penelitian yaitu metode eksperimental dengan rancangan randomized matched two group design. Penelitian dilakukan kepada 50 partisipan mahasiswa Psikologi Universitas Brawijaya dan terdiri dari 2 kelompok yaitu kelompok kontrol dan kelompok eksperim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 1 publication
1
3
0
2
Order By: Relevance
“…Ningrum Baha Lathifah, Amir Hasan Ramli, and Faizah have also researched the relationship of humorous impressions to short-term memory in new students, where they researched Brawijaya University Psychology students in 2015 involving 50 participants with a significant value of 0.001 which is smaller than 0.05, this indicates that there is an effect of humorous impressions on memory abilities. This study proves that there is an effect of humor on memory enhancement [1,2,8,9].…”
Section: Introductionsupporting
confidence: 57%
See 2 more Smart Citations
“…Ningrum Baha Lathifah, Amir Hasan Ramli, and Faizah have also researched the relationship of humorous impressions to short-term memory in new students, where they researched Brawijaya University Psychology students in 2015 involving 50 participants with a significant value of 0.001 which is smaller than 0.05, this indicates that there is an effect of humorous impressions on memory abilities. This study proves that there is an effect of humor on memory enhancement [1,2,8,9].…”
Section: Introductionsupporting
confidence: 57%
“…Based on the results of this study, it can be concluded that the results obtained by researchers have similarities with the results of previous studies that have been conducted by students at Kulliyyah of Islamic Revealed Knowledge and Human Sciences Malaysia, where a significant value was obtained, namely with a p-value of 0.001. Other research was conducted by Ningrum Baha Lathifah, Amir Hasan Ramli, and Faizah, where they researched Brawijaya University Psychology students in 2015 with a significant value of 0.001 [1,8].…”
Section: B the Effect Of Humor Impressions On Short-term Memorymentioning
confidence: 99%
See 1 more Smart Citation
“…Cerita lucu atau humor merupakan informasi yang ringan atau mudah diterima, diserap dimengerti oleh otak siswa, tidak perlu konsentrasi atau focus yang kuat (Darmansyah & Pd, 2011;Lathifah, Ramli, & Faizah, 2016;Taufan, 2018). Biasanya materi-materi pelajaran memerlukan konsentrasi atau focus yang kuat, sedangkan siswa masih belum sadar dengan kondisi yang baru, atau karena kondisi-kondisi lain yang sudah disebutkan sebelumnya di poin permasalahan.Kadang penulis bercerita menggunakan bahasa sunda supaya lebih cepat dimengerti oleh siswa dan siswa yang penting bisa tertawa atau minimal tersenyum.…”
Section: Brain Gym (Senam Otak)unclassified
“…Cerita humor terbukti berhasil menekan tingkat stress pasien di rumah sakit (Awaludin, Santoso, & Novitasari, 2016)h. Selian itu cerita humor dalam bentuk film dapat menurunkan tingkat stres mahasiswa yang sedang menyusun skripsi (Lathifah et al, 2016;Taufan, 2018). Dengan demikian banyak hasil riset yang mendukung pernyataan bahwa cerita humor efektif untuk menurunkan ketegangan dan meningkatkan kenyamanan.…”
Section: Hasil Atau Dampak Yang Dicapaiunclassified